Transthyretin and metallothioneins affect amyloid-beta metabolism and are regulated by glucocorticoids in choroid plexus - Martinho, Ana Isabel de Jesus (2014)
This thesis is structured in six main chapters. The first chapter consists in a concise literature review which includes: a short description of choroid plexus (CP) and its main functions; a characterization of the proteins included in the study, transthyretin (TTR) and metallothioneins (MTs), particularly the isoforms 1/2 and 3 (MT-1/2 and MT-3) (Paper I), mainly focused on their neuroprotective actions; and, a brief description of hormones, namely glucocorticoids, with emphasis on their neurological roles. The second chapter contains the global aims established for the development of this work. The third, fourth and fifth chapters present the results obtained during the course of the PhD work that were published or submitted as original research papers, organized as follows: The third chapter comprises the Paper II – Human metallothioneins 2 and 3 differentially affect amyloid-beta binding by transthyretin. This paper shows that TTR and MT-3 interact and the TTR-MT-2 and TTR-MT-3 interactions affect the TTR binding to amyloid-beta (Aβ) peptide, decreasing or increasing it, respectively. Thus, it is suggested that the effects of these interactions in Aβ metabolism could be relevant in Alzheimer’s disease (AD) context. The fourth chapter includes the Paper III – Stress and glucocorticoids increase transthyretin expression in rat choroid plexus via mineralocorticoid and glucocorticoid receptors. The work presented in this chapter shows the up-regulation of TTR expression, particularly in CP, promoted by glucocorticoids. Furthermore, according to the overall effects of TTR and stress/glucocorticoids in AD, a down-regulation of TTR expression would be expectable, which was not observed. Thus, it is suggested that the increased TTR expression promoted by glucocorticoids, particularly in CP, is not sufficient by itself to inhibit the deleterious effects of these hormones in other brain regions and in the overall AD pathophysiology. The fifth chapter encloses the Paper IV - Glucocorticoids regulate metallothionein-1/2 expression in rat choroid plexus: Effects on apoptosis. Here, it is showed that the expression of MT-1/2 is regulated by glucocorticoids, in liver and CP, in a gender-, tissue- and time exposure dependent manner. In addition, a decrease in the apoptosis in CP cells, upon incubation with anti-MT-1/2 antibody, is demonstrated, indicating that glucocorticoids have protective roles in CP. Finally, the sixth chapter summarizes the general conclusions and future perspectives achieved with this project, regarding the interactions between TTR and MT-2/MT-3 and their effects in TTR-Aβ binding and the role of glucocorticoids in the regulation of TTR and MT-1/2 expressions, particularly in CP.